Emerging Asia: Decoupling or Recoupling - Soyoung Kim; Jong-Wha Lee; Cyn-Young Park (Asian Development Bank (ADB), 2009)
In this paper, we investigate the degree of real economic interdependence between emerging Asia and major industrial countries to shed light on the heated debate over the "decoupling" of emerging Asia. We first document the evolution of macroeconomic interdependence for emerging Asian economies through changing trade and financial linkages at both the regional and global levels. Then, by employing a panel vector autoregression (VAR) model, we estimate the degree of real economic interdependence before and after the 1997/98 Asian financial crisis. Empirical findings show that real economic interdependence increased significantly in the post-crisis period, suggesting "recoupling", rather than decoupling, in recent years. Output shocks from major industrial countries have a significant positive effect on emerging Asian economies. More interestingly, the reverse is also true. Output shocks from emerging Asia (and the People's Republic of China [PRC]) have a significant positive effect on output in major industrial countries. The result suggests that macroeconomic interdependence between emerging Asia and industrial countries has become "bi-directional," defying the traditional notion of the "North–South relationship" as one of "uni-directional" dependence.
hdl:11540/1814
Keywords: E32; F15; F36; F42; 330; Regional integration; decoupling; macroeconomic interdependence; trade and financial market linkages; VAR